Soft tissue augmentation prior to incisor decompensation in Class III malocclusion – preliminary report - Droździk, Agnieszka; Grocholewicz, Katarzyna; Safranow, Krzysztof (Journal of Stomatology, 2017)
Introduction. Even though the role of orthodontic treatment in development of gingival recessions is controversial, teeth movement outside the alveolar “envelope” has been reported as a risk factor for dehiscence, and subsequently for gingival recessions. Aim of the study. To evaluate an increase in thickness and width of buccal attached gingiva after soft tissue augmentation preceding incisor decompensation in Class III malocclusion. Materials and Methods. Eight individuals (non-smokers) with Class III malocclusion underwent soft tissue thickening at the buccal aspects of a total of 30 lower anterior teeth after being qualified for orthodontic treatment. The autogenous subepithelial connective tissue graft (sCTG) harvested from the palate was used and adopted in modified tunnel flap technique. Clinical measurements were performed before the surgical procedure and at three months afterwards, just before commencement of orthodontic treatment. The significance of changes of the studied parameters was evaluated by means of Wilcoxon signed-rank test. Results. Before augmentation all patients presented thin gingival biotype with the mean thickness of 0.6±0.17 mm. At three months postoperatively, the thickness of attached gingiva, as well as its width, increased significantly by 0.75±0.18 mm and 1.95±0.9 mm, respectively (P<0.05). Conclusions. Autogenous sCTG resulted in significant increase in width and thickness of the attached gingiva at the buccal aspects of lower anterior teeth. Transformation of thin gingival biotype into thick one enabled safe implementation of orthodontic treatment in the lower arch in patients with Class III malocclusion. Further research is needed to determine whether prophylactic grafting provides long-term protection against recessions during orthodontic treatment